2011
DOI: 10.1105/tpc.110.081570
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsisMultistress Regulator TSPO Is a Heme Binding Membrane Protein and a Potential Scavenger of Porphyrins via an Autophagy-Dependent Degradation Mechanism  

Abstract: TSPO, a stress-induced, posttranslationally regulated, early secretory pathway-localized plant cell membrane protein, belongs to the TspO/MBR family of regulatory proteins, which can bind porphyrins. This work finds that boosting tetrapyrrole biosynthesis enhanced TSPO degradation in Arabidopsis thaliana and that TSPO could bind heme in vitro and in vivo. This binding required the His residue at position 91 (H91), but not that at position 115 (H115). The H91A and double H91A/H115A substitutions stabilized TSPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(242 citation statements)
references
References 110 publications
(163 reference statements)
5
235
0
2
Order By: Relevance
“…While it was first thought to be nonspecific, recent studies have identified routes for selective autophagy (Xie and Klionsky, 2007;Noda et al, 2008;Behrends et al, 2010). Such selectivity likely provides a critical housekeeping function by removing damaged chloroplasts, mitochondria (mitophagy), and ribosomes (ribophagy), scavenging free porphyrins, clearing unwanted peroxisomes (and possibly glyoxysomes) as their available substrate pools change (pexophagy), degrading ubiquitylated aggregates too large for the 26S proteasome, and possibly even sequestering pathogens that invade the cytosol (Ishida et al, 2008;Wada et al, 2009;Hillwig et al, 2011;Johansen and Lamark, 2011;Vanhee et al, 2011;Youle and Narendra, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While it was first thought to be nonspecific, recent studies have identified routes for selective autophagy (Xie and Klionsky, 2007;Noda et al, 2008;Behrends et al, 2010). Such selectivity likely provides a critical housekeeping function by removing damaged chloroplasts, mitochondria (mitophagy), and ribosomes (ribophagy), scavenging free porphyrins, clearing unwanted peroxisomes (and possibly glyoxysomes) as their available substrate pools change (pexophagy), degrading ubiquitylated aggregates too large for the 26S proteasome, and possibly even sequestering pathogens that invade the cytosol (Ishida et al, 2008;Wada et al, 2009;Hillwig et al, 2011;Johansen and Lamark, 2011;Vanhee et al, 2011;Youle and Narendra, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The cargo receptor (AtNBR1) thus seems to be a selective autophagy substrate, just as the molecules it binds to. 36 The data of Vanhee et al 35 and Svenning et al, 36 however, were not accompanied by an ultrastructural correlate.…”
mentioning
confidence: 80%
“…It thus seems that both the carrier (TSPO) and the carried product become degraded. 35 Another example was described by Svenning et al…”
Section: Autophagy During Degradation Of Specific Proteinsmentioning
confidence: 92%
See 1 more Smart Citation
“…Since SH3P2 has a membrane-remodeling domain, it is likely that an interaction between SH3P2 and ATG8 promotes membrane deformation for developing autophagosome. Recently, selective autophagy has been identified in plants, and the ATG8 family interacting motif has emerged as the molecular basis for ATG8 to recognize cargo(s) or other proteins in regulating autophagy (Suttangkakul et al, 2011;Svenning et al, 2011;Vanhee et al, 2011;Derrien et al, 2012;Floyd et al, 2012;Honig et al, 2012). Since SH3P2 signals were detected inside the vacuole after autophagy induction (Figures 1Bc and 1Bd), such an SH3P2-ATG8 interaction may target SH3P2 for degradation to regulate the turnover of autophagy.…”
Section: Sh3p2 Interacts With the Atg8 Complex And Is Required For Aumentioning
confidence: 99%